"Development and Validation of Academic Motivation Scale among Secondary School Students." (2017)
"The aim of this instrumental study is to develop, validate and measure the psychometric properties of Academic Motivation Scale (AMS) among Secondary School Students in Ibadan metropolis. The study adopted a survey research design. The participants in the study were 432 (228 male; and 204 female) Secondary School Students randomly selected from public secondary schools in Ibadan metropolis. Their age ranged between 12 and 18 years and with mean age of 14.3 years. Confirmatory Factor Analysis (CFA), Pearson’s Product Moment Correlation (PPMC) and Principal Component Analysis (PCA) were used to analysis the data. In purification process, items with low total-item correlation, using 0.3 as a baseline, were discarded. The three-factor CFA loadings were all strong and above .40. For the Model fitness of the Scale to theoretical construct, the Chi-Square Goodness of Fit (GOF) obtained was significant (x2 df = (32) = 227.219; p<.001). Other fitness measure (i.e. RMSEA = <0.08; CFI = 0.90; and Coefficient of Determination (CD) for the residual =0.99 (99%) proved the fitness of the developed scale to the theoretical construct. As expected, the sub-scales of AMS significantly correlated (Intrinsic Motivation and Extrinsic Motivation; r = .370 p<.001) however, Amotivation and Intrinsic Motivation (r = -.094 p>.05); Amotivation and Extrinsic Motivation (r = .022 p>.05) were not significant. The study proved the construct validity of the scale. The internal consistencies of the sub-scales were obtained as: Intrinsic (5 items), a =.83; Extrinsic (5 items) a =.72; Amotivation, (3 items) a =.70; Overall Academic Motivation Scale, (13 items) a =.74. The study has implication for students, motivational mechanism and directions are understood to reduce the number of academic failure and drop-out. It was recommended that Counselling Psychologists should look into the motivational tendencies of helping students in diagnosing problematic areas of those that are not motivated towards academics. "